Including the excluded in South Asia: power, politics and policy perspectives from the region - Sekher, Madhushree; Carciumaru, Radu (Springer eBooks Economics and Finance, 2019)
Introduction: Why is Social Exclusion? A Cross-Country Perspective -- Part 1. Contextualizing Social Exclusion/Inclusion -- Chapter 2. – Inclusion and Marginalization: Concepts and Measures -- Chapter 3. - Persisting Ethnic Tensions in Sri Lanka: Towards a Structural Analysis -- Chapter 4. Social Inclusion/ Exclusion Policy Discourse in Nepal -- Part 2 Inequality and Politics of Inclusion -- Chapter 5. State and Muslims in India : Politics of Inclusion and Exclusion -- Chapter 6. Constitutional Reforms in Sri Lanka: From Majoritarian Control System to Integration and Accommodation? -- Chapter 7 Politics of Public Policy in India: Institutional Internalization of Inequality and Exclusion in Policy Legislation -- Part 3. State, Institutions and Representation -- Chapter 8. Democratic Participation in Bangladesh: Does it Vary Across Ethnicity, Religion and Gender -- Chapter 9. Democratic institutions in Sri Lanka’s local level politics: Challenges to Social Inclusion -- Chapter 10. Intricacies of Nation-States and Incidences of Exclusion -- Part 4. Governance Systems and Opportunities for Inclusion -- Chapter 11. Right to Information: A Viable Institution? Emerging Politics of Accountability -- Chapter 12. Land Alienation and Threats to Livelihoods of Indigenous Populations -- Chapter 13. Manual Scavengers: A Blind Spot in Urban Development Discourse -- Chapter 14. Diversity in Higher Education in India -- Chapter 15. Institutional Responses to Exclusion and Poverty in Highlands